A method for selecting suitable technical solutions to support sustainable riverbank stabilisation. Issue 2 (13th August 2018) - Pinto, António Augusto Sampaio; Fernandes, Luís Filipe Sanches; de Oliveira Maia, Rodrigo Jorge Fonseca
Abstract : The interventions for riverbank stabilisation are among the most common river rehabilitation actions performed in watercourses. However, most of the interventions focus on traditional methods that, although effective at the structural level (i.e., at meeting riverbank stabilisation goals), usually produce negative effects on the ecological status of the river. Thus, due to the increased requirement for sustainable river management solutions, this paper proposes a methodology for selecting suitable technical solutions for riverbank stabilisation. This has two components: (1) characterising, diagnosing and identifying the condition and potential erosion of a riverbank by collecting information at spatial multi‐scale and (2) selecting suitable technical solutions to support sustainable riverbank stabilisation through using evaluation matrices and analysis of the adequacy of each technical solution to the intervention site's conditions and stream flow characteristics. This approach allows a holistic and integrated analysis of the bank erosion problems and the selection of stabilising technical solutions that are best suited from a structural viewpoint. In order to comply with the WFD (Water Framework Directive) on river environment issues, complementary criteria are proposed that help select from the chosen technical solutions those that improve the diversity of habitats as well as mitigate the aesthetic impact with the lowest cost. The methodology was applied to a reach of the Cértima River (located in the Centro region of Portugal), where field visits were performed to help assess the riverbanks' condition as well as to select technical solutions for riverbank stabilisation. As a result, it was possible to select a set of the most suitable technical solutions to ensure physical and hydraulic required functions, to minimise morphological and landscape changes in the banks, and to promote habitat diversity. Abstract : To address the increasing need for sustainable river management, this paper proposes a methodology for selecting suitable technical solutions for riverbank stabilisation. The approach allows a holistic and integrated analysis of bank erosion problems. The most suitable technical solutions support physical and hydraulic function, minimise morphological and landscape changes in the banks and promote habitat diversity.